Online sentiment : machine learning and prediction - Gimpert, Ben (O'Reilly Media, 2011)
"Today's web analyst has moved far beyond funnels and visitors. Automated systems decide who gets what content, and language parsing tries to distill sentiment from millions of online interactions. This panel will look at where web analytics is headed, and how new algorithms and approaches are yielding fresh insights into online commerce."--Resource description page.